2000
DOI: 10.1128/aem.66.4.1305-1310.2000
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Analysis of the Expression of the Styrene Degradation Gene Cluster in Pseudomonas fluorescens ST

Abstract: The effects of different carbon sources on expression of the styrene catabolism genes in Pseudomonas fluorescens ST were analyzed by using a promoter probe vector, pPR9TT, which contains transcription terminators upstream and downstream of the ␤-galactosidase reporter system. Expression of the promoter of the stySR operon, which codes for the styrene two-component regulatory system, was found to be constitutive and not subject to catabolite repression. This was confirmed by the results of an analysis of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…Therefore, it appears that a transcriptional termination signal(s) exists between the paak and the styR genes which prevents readthrough transcription into the regulatory elements styS and styR. This conclusion is supported by recent work involving the promoter region of stySR from the styrene-degrading P. fluorescens ST (Santos et al, 2000). Similarly, it would appear that a transcriptional termination signal(s) exists between styR and styA, which prevents the progress of RNA polymerase into the upper pathway genes beginning with styA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, it appears that a transcriptional termination signal(s) exists between the paak and the styR genes which prevents readthrough transcription into the regulatory elements styS and styR. This conclusion is supported by recent work involving the promoter region of stySR from the styrene-degrading P. fluorescens ST (Santos et al, 2000). Similarly, it would appear that a transcriptional termination signal(s) exists between styR and styA, which prevents the progress of RNA polymerase into the upper pathway genes beginning with styA.…”
Section: Discussionsupporting
confidence: 70%
“…This is in contrast to the styrenedegrading strain Xanthobacter 124X, as growth of the bacterium on PAA results in detectable levels of activity from upper-pathway-associated enzymes styrene oxide isomerase and phenylacetaldehyde dehydrogenase (Hartmans et al, 1989). Furthermore, a recent study with P. fluorescens ST suggested that stySR transcription is constitutive regardless of the carbon source (Santos et al, 2000). Therefore, while a common route for styrene catabolism is observed in many of the bacterial species studied to date, it is clear that there are significant differences in how these degradative pathways are regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, both TodS and TodT proteins are known to be required for the chemotaxis to aromatic hydrocarbons in P. putida F1 (Parales et al, 2000), indicating that the catabolism and microbial behaviour are co-ordinately regulated, and the chemotaxis is probably controlled at the transcriptional level. Similar two-component signal transduction systems have been identified in the pathways of aerobic styrene degradation (O'Leary et al, 2002;Panke et al, 1999;Santos et al, 2000;Velasco et al, 1998), in other forms of aerobic toluene degradation (Mosqueda et al, 1999), and in anaerobic toluene degradation (Coschigano & Young, 1997;Leuthner & Heider, 1998). The sensor proteins found in anaerobic toluene degradation are shorter than TodS and contain two PAS domains and one histidine kinase domain.…”
Section: Discussionmentioning
confidence: 87%
“…1). Catabolic repression on the expression of degradation pathways of aromatic compounds by small organic acid molecules has been reported (34,41,53). The mechanism of catabolic repression of the 2,4,6-TCP degradation pathway in JMP134 by glutamate is unknown, but can occur at the transcriptional level, as reported in Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 94%